Meningkatkan Keterampilan Membuat Lampu Hias Batok Kelapa Melalui Media Video Tutorial - Fadil, Rabbiul; Armaini, Armaini (Jurnal Penelitian Pendidikan Khusus, 2021)
This study discusses efforts to improve the skills of making decorative lamps from coconut shells by deaf children through video tutorials.This research is based on the problem of deaf children who are not yet proficient in making skills, especially in making decorative lamps with coconut shells. With the skill of making decorative lamps from coconut shells using this video tutorial, it is hoped that it can improve children's abilities and these skills can later be useful for deaf children after completing their education. The method used in this article is class action. The data obtained from the results of this study were obtained based on observations, tests, and documentation. This class action was carried out in 2 cycles. In each cycle there are stages of planning, action, observation, and also reflection. The results of the action in the first cycle are R 61%, MF 58%, and F 72%. While in the second cycle the results of R 83%, MF 91%, F 97%. The results obtained after taking action on deaf children, namely the skills of children in making decorative lights on coconut shells using video tutorial media have increased in making decorative lamps from coconut shells at SLB Negeri 1 Lubuk Sikaping.